Optimisation of Healthcare Contracts: Tensions Between Standardisation and Innovation; Comment on "Competition in Healthcare: Good, Bad or Ugly?" - Misja Mikkers; Padhraig Ryan (Kerman University of Medical Sciences, 2016)
An important determinant of health system performance is contracting. Providers often respond to financial incentives, despite the ethical underpinnings of medicine, and payers can craft contracts to influence performance. Yet contracting is highly imperfect in both single-payer and multi-payer health systems. Arguably, in a competitive, multi-payer environment, contractual innovation may occur more rapidly than in a single-payer system. This innovation in contract design could enhance performance. However, contractual innovation often fails to improve performance as payer incentives are misaligned with public policy objectives. Numerous countries seek to improve healthcare contracts, but thus far no health system has demonstrably crafted the necessary blend of incentives to stimulate optimal contracting.